(3eSDhdjI GdeJHhY Yf CYeGd JGHYg aj eLGd Yed eCehQ GdVHW GdbVGFj (B:s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQj hGdYeGfj (B/ s - (3YGFTI HfJ eHGQc Hf SYjO GdOQecjIs; (3SYjO SdjeGf LHQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3GdeSDhdjI GdeOfjI deCehQ GdVHW GdbVGFj gj eSCdI bGfhfjI JJYdb HGdJHYjI GdeGdjI dCaYGdg hbQGQGJg GdJj JSHH VQQG ddZjQ hjJMed JHYjJgG GdeJHhY dg eOfjG hab CMcGe GdeSDhdjI Yf aYd GdZjQ (B. (3MjK jYJHQ eCehQ GdVHW GdbVGFj TNkUG jYed Ydi JfajP bQGQGJ THjgg HGdbQGQGJ GdbVGFjI aj EdRGejI GdeJgejf HGdMVhQ hGdEOdGA HTgGOJge hJSdje CfaSge hZjQg EVGaI Edi bjGeg HJbOje ELQGAGJ JfajPjI(B. (3GdLOjQ HGdPcQ Cf CMO GdLhGfH GdCSGSjI ddeSDhdjI GdeOfjI deCehQ GdVHW GdbVGFj gh Cfg eSDhd Yf GdCVQGQ GdeGOjI Ch GdeGdjI GdJj jJSHH ajgG fJjLI bjGeg HCYeGd GdJMQj aj eQMdI LeY GdGSJOdGdGJ(B. (3jLH Cf jJMdi eCehQ GdVHW HGdObI hGdMPQ aj COGA hGLHGJg dJLfH Cj CVQGQ ZjQ eHQQI ddCaQGO Ch GdeeJdcGJ(B. (3eaghe BNQ ege jJYdb HGdeSDhdjI GdeOfjI gh JahjV GdSdWI(B. (3jYfj gPG Cf eCehQ GdVHW GdbVGFj jJMed GdeSDhdjI Yf JfajP GdChGeQ GdbVGFjI HTcd UMjM haj EWGQ GdUdGMjGJ GdeefhMI dg abW(B. (3EPG JLGhR SdWJg Ch GfJgc GdbhGfjf CKfGA JfajP GdCeQ, jecf Cf jJYQV ddeSGFdI GdeOfjI(B. (3gfGc CjkVG eUWdM BNQ jLH Gdhbha YfOg YfOeG fJMOK Yf eCehQ GdVHW GdbVGFj hgh (B"(3GdEYJOGA(B"(3, aEPG bGe eCehQ GdVHW HELQGAGJ ZjQ eHQQI Ch JLGhR SdWJg hCdMb CPi HTNU Ch eeJdcGJ, jecf ddCaQGO GdeJVQQjf ebGVGJg ddMUhd Ydi JYhjV(B. (3ELeGdkG, GdeSDhdjI GdeOfjI deCehQ GdVHW GdbVGFj JYJeO Ydi GdGdJRGe HGdbhGfjf hGddhGFM hVeGf JfajP GdbQGQGJ GdbVGFjI HObI hOhf EdMGM ZjQ eHQQ(B. (3aj MGdI GdJLGhR Yf gPg GdbhGYO, jecf Cf jchf YQVI ddeSGAdI GdeOfjI heSDhd Yf GdCVQGQ GdeGOjI Ch GdeGdjI GdJj jJSHH ajgG(B. s
The civil liability of a judicial enforcement officer is a legal matter concerning the financial accountability for their actions and decisions, which may cause harm to others, and they bear civil liability as a result, in accordance with the principles of vicarious liability for the actions of another. A judicial enforcement officer is considered an individual responsible for executing decisions similar to judicial orders, compelling defendants to appear, provide testimony, surrender themselves, and other related enforcement procedures. It is worth noting that a fundamental aspect of the civil liability of a judicial enforcement officer is their responsibility for material or financial damages resulting from their investigative activities during the evidence-gathering phase. The enforcement officer must exercise precision and caution in the performance of their duties to avoid any unjustified harm to individuals or property. Another crucial concept related to civil liability is the delegation of authority. This implies that the judicial enforcement officer is accountable for correctly executing judicial orders within the scope of the authority granted to them. If they exceed their authority or violate the law while executing an order, they may face civil litigation. Furthermore, it's essential to consider the term "trespass" when discussing judicial enforcement officers. If an enforcement officer undertakes unwarranted actions or exceeds their authority, causing harm to an individual or property, affected individuals have the option to initiate legal proceedings to seek compensation. In summary, the civil liability of a judicial enforcement officer hinges on their adherence to laws and regulations and ensuring the precise execution of judicial orders without undue haste. In cases of deviation from these principles, they may be susceptible to civil accountability and held responsible for material or financial damage
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQ(B-(3I(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdeOfj, (B2023s
(3HHdjhLQGajG(B: (3UaMGJ (B214-233.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdVHW GdEOGQjs; (3eSFhdjg GdeJHhY Yf GYeGd JGHYg s; (3eSFhdjg GdOhdg Yf GYeGd GdVHW GdbVGFis; (3eGehQ GdVHW GdbVGFis; (3Uag eGehQ GdVHWs; (3GdVHWjgs; (3GdVHW GdGOGQi hGdVHW GdbVGFis; (3GdbGfhf GdYeGfi s; (3NWG eGehQ GdVHW GdbVGFis; (3QSGFd LGeYjIs -- (3cdjI GdMbhbs -- (3GdbGfhf GdeOfjs